The Influence Of Digital Marketing And Information Quality On Purchase Decisions In Zona Nyaman Caf - Mulyadi, Mulyadi; Zalikha, Zalikha; Ariska, Emalia; Yusuf, M (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The purpose of the study was to determine the influence of digital marketing and information quality on purchasing decisions. The design of this study was quantitative descriptive by selecting a sample of 100 visitors to the Caf Zona Nyaman in Bireuen Regency. The results of the study prove that digital marketing and information quality partially, positively and significantly influence consumer purchasing decisions at the Caf Zona Nyaman, and the highest variable that has an influence is information quality.